The Osmoregulatory and the Amino Acid-regulated Responses of System A Are Mediated by Different Signal Transduction Pathways - López-Fontanals, Marta (The Rockefeller University Press, 2003)
The osmotic response of system A for neutral amino acid transport has been related to the adaptive response of this transport system to amino acid starvation. In a previous study (Ruiz-Montasell, B., M. Gómez-Angelats, F.J. Casado, A. Felipe, J.D. McGivan, and M. Pastor-Anglada. 1994. Proc. Natl. Acad. Sci. USA. 91:9569–9573), a model was proposed in which both responses were mediated by different mechanisms. The recent cloning of several isoforms of system A as well as the elucidation of a variety of signal transduction pathways involved in stress responses allow to test this model. SAT2 mRNA levels increased after amino acid deprivation but not after hyperosmotic shock. Inhibition of p38 activity or transfection with a dominant negative p38 did not alter the response to amino acid starvation but partially blocked the hypertonicity response. Inhibition of the ERK pathway resulted in full inhibition of the adaptive response of system A and no increase in SAT2 mRNA levels, without modifying the response to hyperosmolarity. Similar results were obtained after transfection with a dominant negative JNK1. The CDK2 inhibitor peptide-II decreased the osmotic response in a dose-dependent manner but did not have any effect on the adaptive response of system A. In summary, the previously proposed model of up-regulation of system A after hypertonic shock or after amino acid starvation by separate mechanisms is now confirmed and the two signal transduction pathways have been identified. The involvement of a CDK–cyclin complex in the osmotic response of system A links the activity of this transporter to the increase in cell volume previous to the entry in a new cell division cycle.